Perftoran® Inhibits Hypoxia-Associated Resistance in Lung Cancer Cells to Carboplatin - Gamal-Eldeen, Amira M.; Alrehaili, Amani A.; Alharthi, Afaf; Raafat, Bassem M. (Frontiers in Pharmacology, 2022)
Perftoran® (Perfluorodecalin) is an oxygen carrier, and carboplatin is a common chemotherapy drug used ‎worldwide for lung cancer treatment. Hypoxia is one of the factors that induce resistance of lung cancer cells ‎to carboplatin. This study explored the role of Perftoran®, as an oxygen carrier, in lowering the resistance of ‎lung cancer cells to carboplatin through suppression of hypoxia pathway mediators. The effect of Perftoran® ‎on resistance of human lung cancer A549 cells to carboplatin was investigated through evaluation of the ‎following: cytotoxicity by MTT, cell death mode by dual DNA staining, DNA damage by comet assay, DNA ‎platination (DNA/carboplatin adducts) by atomic absorption spectroscopy, hypoxia degree by pimonidazole, ‎HIF-1α/HIF-2α concentrations by ELISA, expression of miRNAs (hypoxamiRs miR-210, miR-21, and miR-181a) ‎by qRT-PCR, and the content of drug resistance transporter MRP-2 by immunocytochemical staining. Results ‎indicated that compared to carboplatin, Perftoran‎‎®/carboplatin decreased cell resistance to carboplatin by ‎potentiating its cytotoxicity using only 45% of carboplatin IC50 and inducing apoptosis. Perftoran‎‎® induced ‎DNA platination and DNA damage index in cells compared to carboplatin alone. Moreover, compared to ‎treatment with carboplatin alone, co-treatment of cells with Perftoran‎‎® and carboplatin inhibited cellular ‎pimonidazole hypoxia adducts, diminished HIF-1α/HIF-2α concentrations, suppressed hypoxamiR expression, ‎and decreased MRP-2. In conclusion, Perftoran® inhibited resistance of lung cancer cells to carboplatin ‎through the inhibition of both hypoxia pathway mediators and the drug resistance transporter MRP-2 and ‎through the induction of DNA/carboplatin adduct formation.‎